AUTOEFFICACY AND THE DEVELOPMENT OF CRITICAL THINKING IN HIGHER EDUCATION STUDENTS BELONGING TO A UNIVERSITY OF LIMA METROPOLITANA. 2023. - Alva Miguel, Walter Hugo (2024)
Abstract     An investigation was carried out whose essential objective was to determine the relationship between self-efficacy and critical thinking in Higher Education students of a University of Metropolitan Lima. To this end, two psychological assessment instruments prepared for such purposes were applied to a sample of 50 Higher Education students: Barraza's Inventory of Academic Self-efficacy Expectations (2010) and the Córdova Critical Thinking Capacity Survey (2021). Both instruments had the proper validity and proven reliability for our environment. These instruments were applied to a sample selected by non- probabilistic, criterial or opinion type sampling. Methodologically, it was a descriptive explanatory investigation of a correlational level, with a quantitative approach, non-experimental design, cross-sectional, which applied parametric statistics (Pearson's Product-Moment Correlation) because it was established by the Kolmogorov - Smirnorv Test. , to determine the normality or otherwise of the scores collected. The statistical procedure was carried out by the Excel 365 Program and the SPSS Version 25 Program for Windows and allowed to verify the hypotheses, in the sense that there was a direct and significant relationship (p= 0.001) between the variables considered. In this sense, the conclusions and the respective recommendations were raised. The respective tables and statistical graphs were elaborated and presented in addition.   Keywords: Self-efficacy, Development of Critical Thinking, Higher Education